Use Of Fibrinogen and Fibrin D-Dimer in Prediction of Arterial Thrombotic Events - Lowe, Gordon D.O.; Rumley, Ann (Thrombosis and Haemostasis, 1999)
There is increasing clinical and laboratory interest in the measurement of both plasma fibrinogen and fibrin D-dimer to predict arterial thrombotic events, such as cardiovascular death, myocardial infarction (MI), stroke, leg ischemia, arterial surgery (e.g., angioplasty, bypass grafting), and postsurgical arterial occlusion. There are several possible reasons for such interest.First, there is substantial evidence from prospective studies that the plasma fibrinogen level is a strong, consistent predictor of such cardiovascular events in people with or without clinically detectable arterial disease. Furthermore, fibrinogen adds to the predictive valve of major conventional risk predictors (e.g., smoking, blood pressure, serum cholesterol) in healthy people (Fig.1).1-7Second, we and others have shown, in several prospective studies, that plasma fibrin D-dimer (measured quantitatively by enzyme-linked immunosorbent assays [ELISAs]) is also a strong, consistent predictor of such cardiovascular events in people with or without clinically detectable arterial disease.8-14 Again, fibrin D-dimer may add to the predictive value of major conventional risk predictors (e.g., smoking, blood pressure, serum cholesterol, plasma fibrinogen) in healthy people (Fig. 2).Third, there are several interactive, plausible, potential biological mechanisms through which increasing plasma fibrinogen levels, which are due to multiple gene-environment interactions, may promote ischemic events. These include increased blood viscosity, atherogenesis, and platelet-fibrin thrombogenesis (Fig. 3). Increased plasma D-dimer levels are a marker of turnover of cross-linked fibrin, whether vascular or extravascular (Fig. 3).Fourth, not only is there more evidence for fibrinogen and D-dimer as predictors of arterial thrombotic events than for other hemostatic or thrombotic variables, but these two assays are more stable and more practical to measure in clinical and epidemiological studies. These tests are also already available in many district hospitals for the diagnosis of disseminated intravascular coagulation (DIC) and, in the case of D-dimer, venous thromboembolism.15,16 As with other major cardiovascular risk factors (e.g., smoking, blood pressure, serum cholesterol), there is a need for standardization of both fibrinogen assays17-23 and D-dimer assays.24Finally, clinical interest in plasma assays of fibrinogen also may increase in the event that ongoing clinical trials of plasma fibrinogen reduction (e.g., with certain fibrates or ancrod) show that such treatments are beneficial.25 Likewise, clinical interest in plasma assays of D-dimer may also increase if future studies show that oral anticoagulant prophylaxis is the most costeffective and risk-effective in people with elevated plasma D-dimer levels, who are normalized by full-dose warfarin.15,19,26-28 This review discusses each of these aspects of fibrinogen and fibrin D-dimer.